Morphology and ultrastructure of the colleterial glands in Myzinum flower wasps (Tiphiidae, Hymenoptera) - da Silva, Marjorie [UNESP]; Justino, Cíntia Eleonora Lopes [UNESP]; Carnimeo, Fernando Henrique [UNESP]; Noll, Fernando Barbosa [UNESP]; Billen, Johan (Elsevier, 2024)
The strategies used by females to ensure the survival of their offspring are one of the key elements in insect reproductive biology. Ectoparasitoid hymenopterans, such as tiphiid wasps, use their ovipositor to deliver a single egg on the host body, where the larva develops. Here we describe the colleterial glands in females of two species of Myzinum and discuss the homology with other glands among Hymenoptera. The glands appear as two large opaque round sac-like structures that are connected to the oviduct. Histological sections revealed a compound gland, with a single layer of class-1 epithelial cells surrounded by a layer of class-3 gland cells, which is uncommon in Hymenoptera. Ultrastructure points to active protein synthesis, consistent with the role of colleterial glands. Despite the consensus that colleterial glands in Hymenoptera evolved with two distinct forms, the venom gland and Dufour's gland, the three glands were present in both Myzinum species. The few studies regarding the structure, function, and homology among the female accessory glands in Hymenoptera do not allow to make conclusive statements about the evolution of these glands. Therefore, the finding in Myzinum is probably the reflection of a lack of information, rather than an exception within Aculeata.
Keywords: Class-1; Class-3; Ectoparasitoid; Female accessory glands; Hymenoptera